A colorimetric probe for the detection of aluminum ions based on 11-mercaptoundecanoic acid functionalized gold nanoparticles. Issue 39 (22nd September 2016) - Zhu, Ruiqi; Song, Jinping; Ma, Qi; Zhou, Ying; Yang, Jun; Shuang, Shaomin; Dong, Chuan
Abstract : An easy, simple and selective colorimetric method for aluminum ions has been developed using 11-mercaptoundecanoic acid functionalized gold nanoparticles (MUA–AuNPs). Abstract : An easy, simple and selective colorimetric method for aluminum ions has been developed using 11-mercaptoundecanoic acid functionalized gold nanoparticles (MUA–AuNPs). The MUA–AuNPs could be induced to aggregate in the presence of Al 3+ ions according to the chelation effect between the carboxyl group and Al 3+, and a color change from red to purple with increasing Al 3+ ion concentration was observed. The plasmon absorbance of the MUA–AuNPs allows the quantitative detection of Al 3+ ions. A sensitive linear correlation existed between the ratio of absorbance at 650 nm to that at 520 nm and the Al 3+ ion concentration ranging from 10 −6 M to 10 −4 M. The detection limit was 5.7 × 10 −7 M, which is below the maximum recommended contamination level of the World Health Organization (WHO) for the aluminum content (7.4 μM) in drinking water. The MUA–AuNPs chelated with Al 3+ showed excellent selectivity in the presence of EDTA compared to other metal ions (Ag +, Ba 2+, Ca 2+, Cd 2+, Cr 3+, Cu 2+, Fe 2+, Hg 2+, Mg 2+, Mn 2+, Ni 2+, Pb 2+ and Zn 2+ ). The proposed method can offer the additional advantage of the efficient determination of Al 3+ ions in drinking water, and the recovery was in the range of 98.5–101.6% with a relative standard deviation below 2%.